Esensi Bunga Altar dalam Liturgi Ibadah Minggu: Studi Kasus tentang Penggunaan Bunga Altar dalam Gereja HKBP Tambun Sari Ressort Bongbongan - Pasaribu, Wando Sampetua; Hasibuan, Ricky Pramono; Marpaung, Morrys Syahputra; Mikael (SUNDERMANN: Jurnal Ilmiah Teologi, Pendidikan, Sains, Humaniora dan Kebudayaan, 2024)
Altar flowers play an important role in various religious traditions, including in the context of the worship liturgy of Lutheran churches today. This paper explores the significance of altar flowers in the liturgical context of the Huria Kristen Batak Protestan (HKBP) church, focusing on their symbolic meaning, aesthetic aspects, and the psychological impact they bring to worship. In worship, altar flowers are visual elements rich in meaning and often used to represent symbols such as the beauty of fertility, new life, or sacrifice, which contribute to the spiritual experience of the congregation. But behind it all, the author has a question from several sources that must be answered by the author regarding how important altar flowers are in the liturgical celebration of worship and what about the flowers that must be given in the altar whether live flowers or otherwise. That way the author will investigate further about the essence and true meaning of altar flowers in the Sunday worship liturgy at the HKBP Tambun Sari Ressort Bongbongan Church. The author then uses the literature method by examining church theological documents and analyzing interview data with congregations at HKBP Tambun Sari Ressort Bongbongan. The results show that regardless of the type of flower chosen, it is important to understand that the essence of using altar flowers is to express deep symbolic and spiritual meaning, in the context of worship.